HUBUNGAN DISMENORE DENGAN GANGGUAN SIKLUS HAID PADA REMAJA DI SMA N 1 MANADO - Juliana, Indah; Rompas, Sefti; Onibala, Franly (Universitas Sam Ratulangi, 2019)
Abstract: Teenagers is the transition period, which characterized by the changes of eitherphysical, psychie, and biological which we call it as puberty. Puberty in teenage girl markedby menstruation, the first year of first menstruation or menarche is time where oftendisruption happened. The Purpose of this research is to know the relationship between thedysmeorrhea with the disturbance of menstrual cycle of the teenage girls in SMA N 1Manado. This research methodology is using the observational design with the CrossSectional approach. The population of this research were 1.103 female students, and thedetermination technique is using Slovin formula. The research sample were 92 people whomet the inclusion criteria. The research instrument are using observation sheet regarding theintensity of pain and menstrual cycle experienced by the respondents. The result of statisticaltest using the Chi Square with the confidence level of 95% (Î±=0.05) with the value p = 0.023,which means p< Î±= 0.05. The conclusion is, the result of this research showing a significantrelation between dysmenorrheal and menstrual cycle disorders in teenage girls in SMA N 1Manado.Keywords : Dysmenorrhea, Mesntrual Cycle, Teenager.Abstrak: Remaja merupakan masa transisi, yang ditandai dengan perubahan baik fisik,psikis, maupun biologis yang kerap disebut pubertas. Pubertas pada remaja putri ditandaidengan menstruasi, tahun-tahun pertama sejak menstruasi pertama kali atau menarchemerupakan masa-masa sering terjadinya gangguan. Tujuan penelitian ini untuk mengetahuihubungan antara dismenore dengan gangguan siklus haid pada remaja di SMA N 1 Manado.Penelitian ini merupakan Metode penelitian kuantitatif dengan desain penelitian yaitu crosssectional. Populasi pada penelitian ini sebanyak 1.103 siswa perempuan, teknik penentuansample menggunakan rumus slovin, didapati sampel sebanyak 92 orang yang memenuhikriteria inklusi. Instrument penelitian ini menggunakan lembar observasi mengenai intenitasnyeri dan siklus haid yang dialami responden. Hasil uji statistic menggunakan uji Chi Squaredengan tingkat kepercayaan 95% ( Î± â‰¤ 0.05), di dapati nilai p= 0.023, yang berarti p< Î±=0.05.Kesimpulan hasil penelitian ini menunjukan adanya, hubungan yang signifikan antaradismenore dengan gangguan siklus haid pada remaja di SMA N 1 Manado.Kata Kunci : Dismenore, Siklus Haid, Remaja.